Species Composition and Economic Value Status of Sea Cucumbers in the Waters of Pulau Banyak, Aceh Singkil - Afiat, Sukra; Suriani, Mai; Kusumawati, Ika; Susetya, Ipanna Enggar (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2024)
The sea cucumber is one of the organisms from the Echinodermata phylum, Holothuridae class. Sea cucumbers (Holothuria) can be found throughout the coastal waters, ranging from shallow tidal areas to deeper waters. This study aims to determine the species composition and economic value of sea cucumbers in Banyak Island waters. This research was conducted from August to September 2023, coinciding in the waters of Banyak Island Aceh Singkil. The research method was carried out by identifying sea cucumber documentation collected directly from local fishermen and conducting direct interviews with collectors who operate to obtain information about the selling price of sea cucumbers. Based on observations, sea cucumbers obtained in the waters of Banyak Island consist of several species in 2 families. The composition of sea cucumber species obtained includes Holothuria atra, H. fuscocinerea, H.edulis, H. fuscopunctata, and Stichopus pseudohorrens. Sea cucumbers found by fishermen have varying economic values, from cheap to expensive prices. The price is influenced by various factors, including the type of sea cucumber and its weight. Each type of sea cucumber has a different selling value, and its weight size is one of the main determining factors in the selling price